Institution and engagement: Vilanova Artigas at the Brazilian Institute of Architects - Dedecca, Paula Gorenstein (Risco - Journal of Architecture and Urbanism, 2016)
The exercise of tracing the biographical path of João Batista Vilanova Artigas articulated with the institutions in which he operates throughout his professional history has only been partially performed by the historiography devoted to the architect, that was dedicated mainly to the understanding of the design and critical spheres of his practice. This article focuses on the architect’s role in the São Paulo Department of the Brazilian Institute of Architects, seeking to understand the relevance of such institutional insertion when analyzing his professional trajectory.